IMPLEMENTASI REVITALISASI PASAR TRADISIONAL (STUDI KASUS REVITALISASI PASAR CICADAS DI KOTA BANDUNG) - , Tatang Hamdani, Drs., Dr. Nunuk Dwi Retnandari ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Along with growing of emulation in service sector and commerce, especially with attendance of modern market, felt concerned about will progressively complicate traditional market. Referring to the mentioned pass/through Decision of Mayor Bandung Number 511.2/Kep.155-Huk/2006, Government Town Bandung continue traditional market revitalitation effort, which is on this which become target is Market Cicadas. But that way as does traditional market in Town Bandung which have been strived for the revitalitation of, finally leaving many problem. Therefore this research aim to to know how Market Cicadas revitalitation implementation and know why happened failure. Used by Research method is method qualitative, as for data obtained to pass/through, interview, documentation and observation. Variable- variable used to reach the target of research is Standard and policy target, Resource, Communications between Organization Executor, Organizational Characteristic of Executor, Condition of Social, Political and Economic and also Attitude or Tendency of Executor. Sixth of the variable selected by because assumed to have as according to research focus. Result of research that especial target of Market Cicadas revitalitation, do not reach result of which is expected. Creating Orderliness, Hygiene and Beauty of (K3) around market environment, fail to be realized. Building Market let do not loaded and all old merchant stand at bay in Place location Relocation of Merchant Whereas (TPPS). And improve efficiency and effectiveness of potency and resource had by area, do not reach result. Earnings contribution from market which is revitalitation even much more is small compared to other market, budget efficiency effort by burdening responsibility to third party in the reality oppositely